Adjustment costs of institutional tax changes from the audit pricing perspective: Empirical evidence from the VAT reform - Binglei Duan; Xinxiao Ma; Taijie Tang; Guojiang Zheng (China Journal of Accounting Research, 2021)
Institutional changes inevitably impose adjustment costs on firms while also generating benefits. However, empirical evidence regarding the adjustment costs of institutional changes is limited, with much of the focus centered on benefits. Using data on China's A-share listed companies from 2010 to 2018 and the nation's staggered adoption of the "business tax to value-added tax reform" (hereafter, "VAT reform") as a natural experiment, we examine the impact of this reform on a particular corporate cost: audit fees. We find audit fees to be 8.11% higher for VAT reform firms than for non-VAT reform firms. This difference does not exist before or after the reform year. That is, it is only observed in the year of VAT reform implementation. This indicates the existence of an adjustment cost specifically related to the VAT reform. Furthermore, we observe larger fee increases among firms audited by Big 4 international audit firms, firms that require more audit work, firms that are more complex, and firms with weak internal controls. From the audit pricing perspective, we provide evidence of the economic consequences of tax reform. The corporate adjustment costs that arise from institutional changes deserve more attention from decision-makers.
Keywords: 650; Audit fees; Audit pricing; Institutional changes; VAT reform